Service productivity, technology and organization - Converting theory to praxis - Esa Viitamo (The Research Institute of the Finnish Economy (ETLA), 2014)
The growth of services - leveraged by the servitization of manufacturing - stresses the urgency of novel approaches and metrics in assessing the performance of services. Building on the statistical and socio-economic paradigms, this paper outlines the microeconomic frame for the integrative analysis of service productivity. The integrative frame is further refined with the complementary premises of the organization theory. Organizations enable link descriptive theorizing of services to the real world contexts that are influenced by uncertainties and the bounded rationality of the business managers. The contingency argument implies that when technology, strategy and the organization of a service firm are mutually consistent, it is possible to address the intangible aspects of service productivity through the tangible characteristics of the firm's organization and the underlying strategy. The organizational method in the analysis of service productivity is illustrated by the productivity regimes of two Nordic banking corporations. The empirical findings suggest that the propositions of the organization theory may have a wider validity across organization types. The paper makes tentative propositions how the productivity regime of a business corporation shows up in its inter-firm relations and network strategies.
Keywords: 330; productivity; service; organization; networks